2015
DOI: 10.1038/srep13065
|View full text |Cite
|
Sign up to set email alerts
|

Formulation Strategy for the Delivery of Cyclosporine A: Comparison of Two Polymeric Nanospheres

Abstract: A wide range of nanoparticles has been explored for the delivery of highly hydrophobic drugs, but very few publications provide comparative data of the performance of different nanoparticles. To address this need, this publication compares poly(lactic-co-glycolic acid) (PLGA) nanoparticles and nanospheres made from tyrosine-derived tri-block copolymers (termed TyroSpheres) for their respective performance as carriers for cyclosporine A (CSA). Using previously reported data on PLGA, we followed similar experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 50 publications
4
41
0
Order By: Relevance
“…Batheja et al demonstrated that a gel formulation of TyroSpheres loaded with Nile red (a hydrophobic model drug) significantly enhanced skin permeation (1.4–1.8 fold) compared to an aqueous dispersion of Nile red-loaded TyroSpheres, both in vitro and in vivo [31]. As these TyroSpheres are suitable only for hydrophobic drugs, they have been extensively studied for the binding and delivery of various therapeutic agents that are hydrophobic and water-insoluble, for example curcumin (unpublished data), cyclosporine A [32], sildenafil [33], rolipram [34] and paclitaxel [30,35,36]. Moreover, these nanospheres are stable for about 6 months, after which time they degrade, most likely through hydrolysis of their ester bonds [28].…”
Section: Nanoparticles For Topical Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…Batheja et al demonstrated that a gel formulation of TyroSpheres loaded with Nile red (a hydrophobic model drug) significantly enhanced skin permeation (1.4–1.8 fold) compared to an aqueous dispersion of Nile red-loaded TyroSpheres, both in vitro and in vivo [31]. As these TyroSpheres are suitable only for hydrophobic drugs, they have been extensively studied for the binding and delivery of various therapeutic agents that are hydrophobic and water-insoluble, for example curcumin (unpublished data), cyclosporine A [32], sildenafil [33], rolipram [34] and paclitaxel [30,35,36]. Moreover, these nanospheres are stable for about 6 months, after which time they degrade, most likely through hydrolysis of their ester bonds [28].…”
Section: Nanoparticles For Topical Therapymentioning
confidence: 99%
“…Drug release from TyroSpheres is dependent on the properties of the drug, the binding and loading efficiencies, and the pH of the solution [37]. For example, Goyal et al showed that the release of cyclosporine A was inversely proportional to the amount of drug loaded in the TyroSpheres [32]. …”
Section: Nanoparticles For Topical Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…The drug-loaded TyroSpheres showed reproducible hydrodynamic diameter of approximately 70 nm and low polydispersity index (0.17), making this polymer the lead candidate evaluated for nanosphere applications (Sheihet et al, 2005). TyroSpheres have been previously evaluated for topical delivery of lipophilic drug/dye molecules (Nile Red (Batheja, 2011 #159), paclitaxel (Kilfoyle et al, 2012), cyclosporine A (Goyal et al, 2015), and adapalene (Ramezanli et al, 2016)) to treat dermatological diseases such as psoriasis and acne. Additionally, theses nanocarriers were able to localize in the hair follicles and release the drug in the pilosebaceous unit (Ramezanli et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Several drug delivery systems capable of sustained release of CsA have been developed, including hydrogel contact lens, 12,13 microspheres, 14 nanoparticles, 15,16 sol-gel, 17 and micelles, 18 some of which may also be used in combination. 19 In our recently published paper, we developed a novel GDD coated with CsA and poly (lactic-co-glycolic acid) polymer (CsA-PLGA) for continuous drug delivery in order to prevent scar formation after glaucoma surgery.…”
mentioning
confidence: 99%